Early results of localised, high-risk prostate cancer treated by moderate hypo-fractionation (70 Gy at 2#x000B7;5 Gy per fraction): 5-year experiences of a moderate hypo-fractionation regimen - Ekkasit Tharavichitkul (2020)
© 2019 Cambridge University Press. Background: Radiotherapy is one of the treatments used to treat prostate cancer, and dose escalation to 74-78 Gy in conventional fractionation is the standard regimen. Currently, according to the hypothesis of low alpha/beta ratio in prostate cancer cells, using hypo-fractionation has been reported in many publications with promising results. This retrospective study was designed to evaluate the implementation of a moderate hypo-fractionation regimen in high-risk prostate cancer in our division.Materials and Methods: Between 2012 and 2017, 40 patients with high-risk, localised prostate cancer were treated by a moderate hypo-fractionation regimen (70 Gy at 2·5 Gy per fraction) with intensity-modulated radiation therapy. The data related to treatment outcomes and toxicities were evaluated.Results: The mean PSA at diagnosis was 86·2 ng/mL (95#x00025; CI 49·9-122·4). Thirty-eight patients received long-term hormonal therapy. Fifty-two percent had a Gleason score of 8-10, and 65#x00025; had an initial PSA #x0003E;20 ng/mL. The mean doses (in EQD2) to the D50#x00025; of PTV, D2#x00025; of organs at risk (bladder, rectum and bowels) were 80, 78·3, 76·4, and 50·2 Gy, respectively. Two patients had biochemical recurrence during the follow-up period.Conclusion: A moderate hypo-fractionation regimen (70 Gy at 2·5 Gy per fraction) is feasible. Our experience found that this regimen yields tolerable, acceptable toxicity profiles in high-risk, localised prostate cancer patients.